SISTEM PENGOLAHAN DATA BANK SAMPAH (STUDY KASUS : BANK SAMPAH BANGKIT PONDOK I NGEMPLAK SLEMAN) - Dhita Prima Kusuma; Yuli Astuti (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
Data processing system is an application to facilitate the processing of data in detail as well as minimize data entry and output errors. With this data processing system allows the presentation of the results of data quickly and accurately as we want. So that agency and the customer more easily and quickly view transactions more secure. The purpose of this paper is to design and makes the required data processing system of Bank Sampah Bangkit Pondok I, because it is still processing the transaction data manually. So that the waste bank manager and customer experience difficulties when conducting transactions securely and minimize data entry errors, and the manager will waste banks more easily create the desired transaction reports. With the data processing system is expected to facilitate the transaction, ease of viewing data required customer and the bank trash. So as to improve security and customer confidence in the bank trash, and the achievement of a more secure transaction of data errors.